Effect of solvation on the vertical ionization energy of thymine: from microhydration to bulk - Ghosh, Debashree; Isayev, Olexandr; Slipchenko, Lyudmila V.; Krylov, Anna I. (Journal of Physical Chemistry A, 2011)
The effect of hydration on the vertical ionization energy (VIE) of thymine was characterized using equation-of-motion ionization potential coupled-cluster (EOM-IP-CCSD) and effective fragment potential (EFP) methods. We considered several microsolvated clusters as well as thymine solvated in bulk water. The VIE in bulk water was computed by averaging over solvent-solute configurations obtained from equilibrium molecular dynamics trajectories at 300 K. The effect of microsolvation was analyzed and contrasted against the combined effect of the first solvation shell in bulk water. Microsolvation reduces the ionization energy (IE) by about 0.1 eV per water molecule, while the first solvation shell increases the IE by 0.1 eV. The subsequent solvation lowers the IE, and the bulk value of the solvent-induced shift of thymine's VIE is approximately -0.9 eV. The combined effect of the first solvation shell was explained in terms of specific solute-solvent interactions, which were investigated using model structures. The convergence of LE to the bulk value requires the hydration sphere of approximately 13.5 angstrom radius. The performance of the EOM-IP-CCSD/EFP scheme was benchmarked against full EOM-IP-CCSD using microhydrated structures. The errors were found to be less than 0.01-0.02 eV. The relative importance of the polarization and higher multipole moments in EFP model was also investigated.

Effective fragment potential method in Q-CHEM: a guide for users and developers - Ghosh, Debashree; Kosenkov, Dmytro; Vanovschi, Vitalii; Flick, Joanna; Kaliman, Ilya; Shao, Yihan; Gilbert, Andrew T. B.; Krylov, Anna I.; Slipchenko, Lyudmila V. (Journal of Computational Chemistry, 2013)
A detailed description of the implementation of the effective fragment potential (EFP) method in the Q-CHEM electronic structure package is presented. The Q-CHEM implementation interfaces EFP with standard quantum mechanical (QM) methods such as HartreeFock, density functional theory, perturbation theory, and coupled-cluster methods, as well as with methods for electronically excited and open-shell species, for example, configuration interaction, time-dependent density functional theory, and equation-of-motion coupled-cluster models. In addition to the QM/EFP functionality, a fragment-only feature is also available (when the system is described by effective fragments only). To aid further developments of the EFP methodology, a detailed description of the C++ classes and EFP module's workflow is presented. The EFP input structure and EFP job options are described. To assist setting up and performing EFP calculations, a collection of Perl service scripts is provided. The precomputed EFP parameters for standard fragments such as common solvents are stored in Q-CHEM's auxiliary library; they can be easily invoked, similar to specifying standard basis sets. The instructions for generating user-defined EFP parameters are given. Fragments positions can be specified by their center of mass coordinates and Euler angles. The interface with the IQMOL and WEBMO software is also described. (c) 2013 Wiley Periodicals, Inc.
Keywords: effective fragment potential; EFP library; hybrid QM; IQMOL; MM; modular code; nonempirical force field; Q-CHEM; WEBMO

Electrostatics determine vibrational frequency shifts in hydrogen bonded complexes - Dey, Arghya; Mondal, Sohidul Islam; Sen, Saumik; Ghosh, Debashree; Patwari, G. Naresh (Physical Chemistry Chemical Physics, 2014)
The red-shifts in the acetylenic C-H stretching vibration of C-H center dot center dot center dot X (X = O, N) hydrogen-bonded complexes increase with an increase in the basicity of the Lewis base. Analysis of various components of stabilization energy suggests that the observed red-shifts are correlated with the electrostatic component of the stabilization energy, while the dispersion modulates the stabilization energy.

Effect of sequence on the ionization of guanine in DNA - Chakraborty, Rahul; Ghosh, Debashree (Physical Chemistry Chemical Physics, 2016)
The accurate estimation of the ionization energies and understanding the nature of the ionized states of the nucleic acid bases (NABs) are crucial to the understanding of the DNA damage mechanism. The vertical ionization energy (VIE) of guanine is the lowest among the NABs and the ionization energies are strongly affected by the environment, such as solvation and characteristics of nearby NABs. Therefore, we investigate the sequence dependence of the VIEs of guanine in B-DNA. We use the equation of motion coupled cluster method for the estimation of ionization potential with single and double excitations (EOM-IP-CCSD) and density functional theory with dispersion corrected omega B97x-D for the estimation of VIEs. A significant amount of non-additivity or cooperativity, directly proportional to charge delocalization, is noticed in the change in VIE due to the interaction with the nearby NABs. While the change in VIE due to base pairing originates predominantly from charge-dipole interactions, stacking between base pairs is a more complicated balance of dispersion and charge-dipole interactions as well as stabilization due to the delocalization of the positive charge. The long range interactions are however dominated by 1/r(3) distance dependence which shows the major role played by charge-dipole interactions. The extent of localization of positive holes on guanine is also estimated for various sequences.

Effect of solvation on electron detachment and excitation energies of a green fluorescent protein chromophore variant - Bose, Samik; Chakrabarty, Suman; Ghosh, Debashree (Journal of Physical Chemistry B, 2016)
Hybrid quantum mechanics/molecular mechanics (QM/MM) is applied to the fluorinated green fluorescent protein (GFP) chromophore (DFHBDI) in its deprotonated form to understand the solvatochromic shifts in its vertical detachment energy (VDE) and vertical excitation energy (VEE). This variant of the GFP chromophore becomes fluorescent in an RNA environment and has a wide range of applications in biomedical and biochemical fields. From microsolvation studies, we benchmark (with respect to full QM) the accuracy of our QM/MM calculations with effective fragment potential (EFP) as the MM method of choice. We show that while the solvatochromic shift in the VEE is minimal (0.1 eV blue shift) and its polarization component is only 0.03 eV, the effect of the solvent on the VDE is quite large (3.85 eV). We also show by accurate calculations on the solvatochromic shift of the VDE that polarization accounts for similar to 0.23 eV and therefore cannot be neglected. The effect of the counterions on the VDE of the deprotonated chromophore in solvation is studied in detail, and a charge-smearing scheme is suggested for charged chromophores.

Effects of the benzoxazole group on green fluorescent protein chromophore crystal structure and solid state photophysics - Ghodbane, Abdelhamid; Fellows, W. Brett; Bright, John R.; Ghosh, Debashree; Saffon, Nathalie; Tolbert, Laren M.; Fery-Forgues, Suzanne; Solntsev, Kyril M. (Journal of Materials Chemistry C, 2016)
Four benzoxazole-substituted GFP chromophores that differ by the length of their alkyl chain (from C1 to C12) were synthesized. In solution, the four compounds showed identical spectroscopic behavior, emitting blue light with moderate quantum yield. In the solid state, the butyl, pentyl and dodecyl derivatives strongly emitted orange light, while the methyl derivative was only weakly emissive. Based on the X-ray data and DFT calculations, emission in the solid state was explained by the formation of excimers. A very unusual ``hot-dog''-type excimer was found for the dodecyl derivative, in which two overlapping chromophores are separated by an alkyl chain.

Extension of the effective fragment potential method to macromolecules - Gurunathan, Pradeep Kumar; Acharya, Atanu; Ghosh, Debashree; Kosenkov, Dmytro; Kaliman, Ilya; Shao, Yihan; Krylov, Anna I.; Slipchenko, Lyudmila V. (Journal of Physical Chemistry B, 2016)
The effective fragment potential (EFP) approach, which can be described as a nonempirical polarizable force field, affords an accurate first-principles treatment of noncovalent interactions in extended systems. EFP can also describe the effect of the environment on the electronic properties (e.g., electronic excitation energies and ionization and electron-attachment energies) of a subsystem via the QM/EFP (quantum mechanics/EFP) polarizable embedding scheme. The original formulation of the method assumes that the system can be separated, without breaking covalent bonds, into closed-shell fragments, such as solvent and solute molecules. Here, we present an extension of the EFP method to macromolecules (mEFP). Several schemes for breaking a large molecule into small fragments described by EFP are presented and benchmarked. We focus on the electronic properties of molecules embedded into a protein environment and consider ionization, electron-attachment, and excitation energies (single-point calculations only). The model systems include chromophores of green and red fluorescent proteins surrounded by several nearby amino acid residues and phenolate bound to the T4 lysozyme. All mEFP schemes show robust performance and accurately reproduce the reference full QM calculations. For further applications of mEFP, we recommend either the scheme in which the peptide is cut along the C-alpha-C bond, giving rise to one fragment per amino acid, or the scheme with two cuts per amino acid, along the C-alpha-C and C-alpha-N bonds. While using these fragmentation schemes, the errors in solvatochromic shifts in electronic energy differences (excitation, ionization, electron detachment, or electron-attachment) do not exceed 0.1 eV. The largest error of QM/mEFP against QM/EFP (no fragmentation of the EFP part) is 0.06 eV (in most cases, the errors are 0.01-0.02 eV). The errors in the QM/molecular mechanics calculations with standard point charges can be as large as 0.3 eV.

Electrostatic origin of the red solvatochromic shift of DFHBDI in RNA spinach - Bose, Samik; Chakrabarty, Suman; Ghosh, Debashree (Journal of Physical Chemistry B, 2017)
Interactions with the environment tune the spectral properties of biological chromophores, e.g., fluorescent proteins. Understanding the relative contribution of the various types of noncovalent interactions in the spectral shifts can provide rational design principles toward developing new fluorescent probes. In this work, we investigate the origin of the red shift in the absorption spectra of the difluoro hydroxybenzylidene dimethyl imidazolinone (DFHBDI) chromophore in RNA spinach as compared to the aqueous solution. We systematically decompose the effects of various components of interactions, namely, stacking, hydrogen bonding, and long-range electrostatics, in order to elucidate the relative role of these interactions in the observed spectral behavior. We find that the absorption peak of DFHBDI is red-shifted by similar to 0.35 eV in RNA relative to the aqueous solution. Earlier proposals from Huang and co-workers have implicated the stacking interactions between DFHBDI and nucleic acid bases to be the driving force behind the observed red shift. In contrast, our findings reveal that the long-range electrostatic interactions between DFHBDI and negatively charged RNA. make the most significant contribution. Moreover, we notice that the opposing electrostatic fields due to the RNA backbone and the polarized water molecules around the RNA give rise to the resultant red shift. Our results emphasize the effect of strong heterogeneity in the various environmental factors that might be competing with each other.